Differentiation and intimate partner violence - Likcani, Adriatik (Kansas State University, 2013)
This study explored the impact of differentiation of self on Intimate Partner Violence (IPV). First, the study determined if differentiation of self in a relationship added to the variance accounted for by the known risk factors including relational satisfaction, marital conflict, romantic jealousy, depression, anxiety, and attitude about violence towards women. Second, it examined the moderating effect of gender on the relationship between differentiation of self and IPV. Results indicated that differentiation of self in a relationship is a predictor of perpetration of intimate partner violence in relationships even after controlling for other known risk factors. Results also indicated that gender did not moderate the relationship between differentiation of self and perpetration of violence.
Keywords: Differentiation; Intimate partner violence; IPV; Domestic violence; Family systems theory; Behavioral Sciences (0602); Clinical Psychology (0622); Cognitive Psychology (0633); Counseling Psychology (0603); Individual & Family Studies (0628); Psychology (0621); Psychology, Behavioral (0384); Social Psychology (0451); Social Research (0344); Social Sciences Education (0534); Social Work (0452); Sociology (0626)